PRESIDENTIAL SYMPOSIUM: COMPARATIVE AGING AROUND THE WORLD—THE GATEWAY TO GLOBAL AGING. (11th November 2018) - Lee, J; Weir, D
Abstract: International comparisons of the aging experience can provide natural laboratories that aide in understanding the universalities as well as the differences in the process of aging. The last two decades have seen the development of longitudinal aging studies in over 40 countries of the world. Many of these studies have been harmonized within the Gateway to Global Aging in order to encourage and facilitate comparative analysis across countries. Each of the four papers in this session uses harmonized data to compare the aging experience in multiple countries. Topics include healthy life expectancy, cognitive aging, life satisfaction, and use of health care at the end of life.